Super adjacent - Cestari, Crystal (Poppy, Little, Brown and Company, 2021)
Claire's dream internship with Warrior Nation is quickly complicated by a budding relationship with new superhero Joy, and when supervillains strike, Claire must team up with disillusioned Bridgette to save the day.